Depolymerization of microcrystalline cellulose to value added chemicals using sulfate ion promoted zirconia catalyst. (November 2016) - Kassaye, Samuel; Pagar, Chetan; Pant, Kamal K.; Jain, Sapna; Gupta, Rajat
Highlights: Synergetic effect of [BMIM] Cl and SZ catalyst depolymerised MCC with 57% TRS yield. Bifunctionality of SZ improved the depolymerization of MCC and dehydration of sugar. Hydrolysis is influenced by temperature, time, catalyst loading and co-solvent type. Abstract: The transformation of lignocellulosic biomass to value added chemicals in a synergetic effect of sulfated zirconia (SZ) catalyst and ionic liquid was found to effectively depolymerize microcrystalline cellulose (MCC) to sugars and dehydrate sugars to 5-hydroxylmethylfurfural (5-HMF) and levulinic acid (LA). SZ was catalyst synthesized by wet impregnation method with predetermined concentration of sulphuric acid and then characterized using techniques such as X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), BET-surface area analyzer, thermo-gravimetric analysis (TGA) and temperature programmed desorption of ammonia (Ammonia-TPD). SZ catalyst was effective in depolymerizing MCC yielding a maximum of total reducing sugar (TRS) of 57% (38% glucose and 14% fructose), 9.5% LA and 5.1 of 5-HMF at a temperature of 180 °C and 3 h of depolymerization time. In addition, SZ was tested for dehydration of glucose and fructose and a yield of 26% and 62% of 5-HMF were obtained, respectively.